Bumblefoot in free-living black swan (Cygnus atratus) in Mozambique - dos Santos, Ivan Felismino Charas [UNESP]; Da Silva, Bruna Martins [UNESP]; Ferro, Barbara Sardela [UNESP]; de Castro Martins, David José [UNESP]; Ferreira, Gustavo Manea [UNESP]; Branco, Marina Paiva [UNESP]; de Siqueira Silva Júnior, José Ivaldo [UNESP]; de Fátima Solano Blazizza, Mayra [UNESP]; Sato, Thais Hamae [UNESP]; Rahal, Sheila Canevese (My University, 2018)
Background: Black Swan (Cygnus atratus Linnaeus 1766) is an aquatic bird native to Australia and non-migratory birds. Bumblefoot is a chronic, progressive, degenerative and granulomatous disease that affects the plantar region and causes inflammation and degenerative changes in plantar tissues. Given that bumblefoot incidence in free-living wild birds is low and that the literature lacks publications about bumblefoot in free-living Black Swans, the aim of the current study is to describe the first bumblefoot case reported in a free-living Black Swan (Cygnus atratus) in Mozambique who was subjected to surgical procedure. Case: An adult intact Black Swan (Cygnus atratus) weighing 7.2 kg was presented to Veterinary Hospital of the Veterinary Medicine School, Mozambique with reluctance to support the left hind limb. Water intake was not unsettled and urine and feces were normal. A brown mass with 3 cm diameter approximately was identified in the footpad of the left hind limb; there were local bleeding and ulcers and pain. Footpad radiographic images of the left hind limb showed no abnormalities in the bone tissue. An incisional biopsy was performed with patient under sedation. The cytopathological examination was suggestive of bumblefoot. An excisional biopsy was performed with patient under anesthesia. The mass was excised with surgical margin of 1 cm and the local was subjected to debridement. The sample was sent to histopathological examination. The histopathological examination confirmed a chronic Bumblefoot Type 2. The patient started to support the left hind limb three days after surgery and twenty days after surgery, the footpad sutures were removed. Fifty days after the surgical procedure the patient was released in the site it was rescued. Discussion: The present case report describes the clinical and diagnostic treatments, as well as the histopathological findings about a chronic bumblefoot type 2 diagnosed in a free-living Black Swan. Bumblefoot is uncommon in free-living wild birds, since they have the possibility of choosing a habitat that allows natural plantar desquamation. There are no reports in the literature describing bumblefoot in free-living Black Swan (Cygnus atratus) in Mozambique. Bumblefoot occurrence in birds can change depending on body mass and age. Older and heavier birds are the most affected by the condition, which is associated with immune defense decrease and with increased pressure on the footpad region. Toxins produced by microorganisms inhibit phagocytosis and coagulase stimulates the formation of a fibrin barrier that isolates them from the action of the animal's immune defense in the acute phase of bumblefoot. The present reported case was classified as chronic bumblefoot type 2 given the lesion features: infection of the dermis without purulent content. Chronic bumblefoot reports highlight the animals' reluctance to support the limb and pain, similar to the clinical signs of the present report. Radiographic examinations allowed assessing bone commitment and histopathological exams enabled the final diagnosis. Treatment modalities have already been implemented in bumblefoot in aquatic birds, including antibiotic therapy, surgical debridement and photodynamic therapy, however, surgical therapy was better than the clinical one. The literature recommends an excisional biopsy with debridement of the lesion in birds due to the reduction of the antigenic load and inflammatory debridement. In conclusion, bumblefoot was a rare condition in free-living wild birds; its clinical diagnosis must be made through cytopathological examination and confirmed through histopathological exams. Surgery is recommended as therapy of choice.
Pododermite em Cisne Negro (Cygnus atratus) em Moçambique
Keywords: Africa; Bird; Mozambique; Plantar tissue; Surgery